2019
DOI: 10.1016/j.jacr.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities for Lung Cancer Screening in Rural America

Abstract: Rural populations have higher rates of smoking and both lung cancer incidence and mortality compared with their urban peers. As such, it is imperative that high-risk, rural populations have access to recommended low-dose CT (LDCT) screening, which can detect lung cancer at an earlier, more treatable stage. Data from the 2015 National Health Interview Survey, a nationally representative survey, were analyzed to assess nonmetropolitan-metropolitan and geographic differences in LDCT utilization among screening-el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 33 publications
4
27
1
Order By: Relevance
“…Although rural areas are associated with poorer health outcomes than urban areas (25), we must also consider the urban-rural paradox, which suggests that among urban residents, greater distance to health care facilities is inversely associated with receiving care, but among rural residents, greater distance is positively associated with receiving care (26). Using 2015 data, Odahowski et al found that LDCT screening uptake was similar across metropolitan and nonmetropolitan counties, although low rates in both areas (<4%) make it difficult to understand why uptake is similar and whether the similarity will be maintained over time (27).…”
Section: Discussionmentioning
confidence: 99%
“…Although rural areas are associated with poorer health outcomes than urban areas (25), we must also consider the urban-rural paradox, which suggests that among urban residents, greater distance to health care facilities is inversely associated with receiving care, but among rural residents, greater distance is positively associated with receiving care (26). Using 2015 data, Odahowski et al found that LDCT screening uptake was similar across metropolitan and nonmetropolitan counties, although low rates in both areas (<4%) make it difficult to understand why uptake is similar and whether the similarity will be maintained over time (27).…”
Section: Discussionmentioning
confidence: 99%
“…A disproportionate amount of the screening-eligible population resides in rural areas, 14 yet these areas often do not provide sufficient access to LCS facilities. 47,48 While some participants in this study indicated they would travel long distances to get screened for lung cancer, those participants tended to be highly motivated.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 In 2016, the LCS rate in the United States was only 1.9%, 12 which likely saved about 233 lives-12 017 fewer than if everyone eligible were screened. 13 Despite rural areas having a disproportionately higher percent of people eligible for screening, LCS rates are no higher in rural areas than in other parts of the country, 14 and rural areas have unique challenges in getting patients screened. 4,14 Little is known about why LCS uptake remains so low, though there are likely compounding patient, facility, system, and health care provider factors, 4,15 including skepticism among the health care community 16 and difficulty identifying patients who meet the criteria to be screened.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the US lung cancer screening centres are geographically maldistributed relative to the rural-urban and regional need. 76…”
Section: Rural and Remote Locationsmentioning
confidence: 99%
“…This is likely to be replicated in lung cancer screening unless models of care that are more disposed towards rural dwellers can be designed and implemented. Currently, the US lung cancer screening centres are geographically maldistributed relative to the rural–urban and regional need 76 …”
Section: Smokers As a Target Group Are ‘Hard To Reach’mentioning
confidence: 99%